Social patterns influencing the adoption of mobile phones in the farming community - Lubua, Edison Wazoel (Department of Information Systems, 2017)
The study determined the influence of social patterns on the adoption of mobile phones in agricultural society. It targeted small farmers in the African society, and its population was drawn from Tanzania. The study was conducted with the knowledge that small (peasant) farmers make up a large component of the African population. Enhancing the economic performance of farmers would improve the general economy of the addressed society, and eventually be translated to the Gross Domestic Product. On this basis, the adoption of ICTs (mobile phones in particular) would enhance the farmers' ability to access the right information for their day-to- day activities. Therefore, this was the reason why this study decided to find out whether social factors contribute to the adoption of mobile phones in the farming society. There are numerous models regarding the adoption of a new innovation by users. Nevertheless, models discussed in this study had social factors as a common aspect. Conceptually the study considered farmers' spending ability, the influence of the success of others, and the adoption on demand, as the factors within social variables. Other variables included the perceived economic benefits, the perceived intention to use, and the rate of use (use behaviour). Moreover, it is necessary to acknowledge that the study was conducted objectively, and embraced hypothesis testing as the basis for decision making. Data were obtained through a survey questionnaire. Generally, the findings of the study suggested the followings: Farmers' spending ability relates to their willingness to learn new mobile tools, peer influence relates to the intention to learn, adoption on demand influences the perceived usefulness of mobile tools, and the perceived usefulness relates with the rate of mobile use. The general view of this study is that social factors influence the adoption of mobile phones in the farming community, either directly or indirectly. Therefore, these factors may be applied to enhance the adoption of mobile phones in the farming community for improved production.